Crisis - Tabori, George 1914-2007; Rózsa, Miklós 1907-1995 (Turner Entertainment Co., 2010)
"While on vacation in a Latin American country, an American neurosurgeon and his wife become tangled in a revolutionary uprising against a tyrannical dictator." [imdb.com]
Original: USA 1950
Bildformat 1.33:1
Keywords: Film; DVD-Video